Evaluación de la remoción de nitratos por electrocoagulación (2018)
The project seeks to evaluate the removal of nitrates by means of electrocoagulation, this being an unconventional technology in the treatment of water. Economic activities are an important part of pollution due to agricultural practices, such as fertilizer, irrigation and organic waste, are the main factor of alteration of the quality of ground and surface water. Electrocoagulation is a technology that uses electricity for the effective removal of a wide variety of contaminants in water such as oils, phenols, heavy metals, nitrites, nitrates and fluorides, among others. This electrochemical process has a series of reactions in which the anode involves being sacrificed to generate cations necessary for coagulation, as well as natural gases that help the flotation.